Fallen women - Dallas, Sandra (St. Martin's Press, 2013)
"The New York Times bestselling author of True Sisters and Prayers for Sale is at her best with a novel about a woman's search for information surrounding the death of her estranged sister. It's the spring of 1885 when wealthy New York socialite Beret Osmundsen first sets foot in a Denver police station. Just days before, she received the terrible news of the death of her estranged younger sister, Lillie. The telegram from her aunt and uncle was brief, stating only that Lillie had passed away suddenly and there was no need for Beret to make the long trip west. Soon, a sordid story is revealed when Beret comes across a scandal sheet with the details of a brutal murder of a prostitute named 'Lillie Brown' in the brothel where she lived. Upon a closer read, Beret becomes convinced that 'Lillie Brown' was in fact her sister, and her murderer has not been caught. Her investigation takes her from the dangerous, seedy underworld of Denver's tenderloin to the highest levels of Denver society. Along the way, Beret learns the depths of Lillie's depravity and must reconcile these with her memories of the innocent young girl of their youth, all while never losing site of finding the murderer. With the help of detective Mick McCauley, Beret ultimately unearths the truth about the sister she couldn't save and exposes the darkest side of Gilded Age ambition in the city in the process"--